Association Between Parenting Style and Socio-Emotional and Academic Functioning in Children With and Without ADHD: A Community-Based Study. Issue 5 (March 2019) - Bhide, Sampada; Sciberras, Emma; Anderson, Vicki; Hazell, Philip; Nicholson, Jan M.
Objective: In a community-based study, we examined parenting style and its relationship to functioning in 6- to 8-year-old children ( n = 391; 66.2% male) with ADHD ( n = 179), compared with non-ADHD controls ( n = 212).Method: Parenting style was assessed using parent-reported (93.5% female) measures of warmth, consistency, and anger. Child socio-emotional and academic functioning was measured via parent- and teacher-reported scales, and direct academic assessment.Results: Parents reported less consistency and more anger in the ADHD group compared with non-ADHD controls, with no differences in warmth. Parenting warmth, consistency, and anger were associated with parent-reported aspects of socio-emotional functioning for children with ADHD and non-ADHD controls, after adjusting for socio-demographic variables, externalizing comorbidities, and ADHD symptom severity. Parenting style was no longer related to academic functioning and most teacher-reported outcomes after adjustment.Conclusion: Generic parenting interventions that promote warm, consistent, and calm parenting may help alleviate socio-emotional impairments in children with ADHD.